(untitled) (Economic studies journal, 2023)
Human trafficking crimes are among the crimes that transcend the borders of one country, as it affects many countries, as it is of an international nature, so that it casts its effects on all societies, whether developed or underdeveloped, that are the source of this trade, as it affects many countries that are known Transit countries, as well as countries receiving this trade, and this study aims to define the concept of this phenomenon, its causes and el. The researcher came to many conclusions and recommended in his findings that measures be taken to reduce the spread of this phenomenon and ways to combat it, as well as the need to search for international strategies to combat this crime within the framework of coordination between all parties in the international community to combat it and address its causes. Several outcomes have been obtained, including the following: A- The importance of enacting deterrent legislative measures to curb the spread of these phenomena. B- The necessity to conduct research and develop worldwide strategies to combat this crime, within the framework of international community coordination to battle it and address its causes. C- The importance of enacting legal legislation at the national level and including what is agreed upon in international agreements in that legislation, as well as at the international level by concluding agreements and treaties in this regard, and urging the enactment of legislation at the national level in accordance with international standards regarding addressing the causes of these phenomena and limiting their spread. E- Urging governments to assist victims of these crimes and to protect their human rights, whether from a legal, economic, or health standpoint, and to include them in legislation before their local authorities as well as other countries’ authorities.